Implementasi Pengendalian Konflik Keluarga bagi Relasi Suami Istri Kristen - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
Conflict arises in every marriage. It is a part of life that naturally occurs in every household, anywhere, including Christian marriages, even though they are blessed in the church, they are not immune to conflict free. Controlling conflict has an impact on whether the husband and wife relationship is strong in Christian marriages, so knowing the sources of triggers or causes of conflict in a Christian marriage family is very important so that we can anticipate and take conflict resolution in appropriate ways. The method in writing this journal is carried out by analyzing relevant sources from books and research literature, so that application suggestions are obtained for increasing the stronger relationship between husband and wife because they can control conflict well. Husband and wife need to put the reconciliation process that Allah created for the husband and wife relationship to be applied in all marital relations that are disturbed or even damaged.